Edukasi Personal Hygiene Organ Reproduksi Pada Ibu Hamil Tentang Pencegahan Infeksi Saluran Kemih - Sah Marianta Ginting; Rani Cahya; Karunia Febriani; Kiki Intan Nuraini (STIKES Columbia Asia Medan, 2026)
Urinary tract infection (UTI) remains one of the most frequent bacterial complications during pregnancy and is closely associated with adverse maternal and neonatal outcomes such as pyelonephritis, preterm labor, low birth weight, and neonatal sepsis. Inadequate personal hygiene of the reproductive organs is a modifiable determinant of UTI, yet knowledge among pregnant women in rural Indonesian communities is still limited. This community service activity aimed to improve pregnant women's knowledge of reproductive organ personal hygiene as a preventive strategy against UTI. The activity was conducted on 25 June 2026 at the Village Hall of Kota Tebing Tinggi, North Sumatra, and involved 32 pregnant women. The intervention combined lectures, leaflet distribution, demonstration, discussion, and hand-hygiene simulation, and used a validated pretest-posttest instrument to measure knowledge change. Results showed a substantial increase in good-level knowledge from 34.4% before the intervention to 90.6% afterwards, while the poor category decreased from 21.9% to 0%. Participant satisfaction was high (mean 92.5%). The activity demonstrates that structured hygiene education is effective and feasible for integration into routine antenatal services at the primary care level.